2019
DOI: 10.1371/journal.ppat.1007164
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium male gametocyte development and transmission are critically regulated by the two putative deadenylases of the CAF1/CCR4/NOT complex

Abstract: With relatively few known specific transcription factors to control the abundance of specific mRNAs, Plasmodium parasites may rely more on the regulation of transcript stability and turnover to provide sufficient gene regulation. Plasmodium transmission stages impose translational repression on specific transcripts in part to accomplish this. However, few proteins are known to participate in this process, and those that are characterized primarily affect female gametocytes. We have identified and characterized… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(79 citation statements)
references
References 68 publications
(102 reference statements)
7
70
0
Order By: Relevance
“…1E-H ). These cytosolic puncta did not overlap with aldolase or DAPI, whcih is consistent with previous reports for the P. yoelii orthologue, PyCCR4 [18] and the other three PfCCR4 paralogues [39]. This intracellular localization is consistent with other eukaryotic species suggesting the function of PfCCR4-NOT complex in posttranscriptional regulation via interactions with mRNA in the parasite cytoplasm.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1E-H ). These cytosolic puncta did not overlap with aldolase or DAPI, whcih is consistent with previous reports for the P. yoelii orthologue, PyCCR4 [18] and the other three PfCCR4 paralogues [39]. This intracellular localization is consistent with other eukaryotic species suggesting the function of PfCCR4-NOT complex in posttranscriptional regulation via interactions with mRNA in the parasite cytoplasm.…”
Section: Resultssupporting
confidence: 91%
“…The co-immunoprecipitation studies confirmed physical interaction of PfCAF40 with PfNOT1.1, PfNOT1.2, PfCAF1 and PfNOT4; PfCAF1 with PfCCR4; and either of the PfNOT1.1 or PfNOT1.2 with PfCAF40 and PfCAF1, respectively. On the other hand PfNOT4 failed to co-immunoprecipitate PfNOT1.1 and PfNOT1.2 (Table 1, top panel) , which is consistent with the transient character of this subunit with the CCR4-NOT complex previously demonstrated in Drosophila [52], human [53] and P.yoelii [18]. However, our data showed that PfNOT4 does associate with the PfCCR4-NOT complex given its interaction with CAF40 and possibly CAF1.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations